STRATEGI PENGEMBANGAN PARIWISATA DESA LEUWEUNGGAJAH KECAMATAN CILEDUG KABUPATEN CIREBON - Toni Ari Wibowo; Agung Setiawan; Syafruddin Rais; Nubi Adzrul Idzihart (PUSLITABMAS - BATAM TOURISM POLYTECNIC, 2023)
Leuweunggajah Village, Ciledug Subdistrict is one of the villages that has the potential of objects and tourist attractions through the development of Islam which is an attraction so that it is necessary to analyze tourism potential through tourism development strategies in Leuweunggajah Village. This research was conducted in Leuweunggajah village to obtain a potential and mapping of tourism objects and attractions in Leuweunggajah village so that it can create a tourism development strategy from the potential of tourism objects and attractions in Leuweunggajah village. This research method is done by observation, interview, and documentation in data collection. The results of data collection from observations, interviews, and documentation can be described using SWOT analysis and continued analysis of priority strategies based on internal strategic factors and analysis of external strategic factors in tourism development as a tourist village. Research conducted in Leuweunggajah village has 7 (seven) potential objects and tourist attractions, namely: Baitussu'ada Mosque, Sacred Well, Habib Toha Tomb, Friday Kliwon Tradition, Wanit Tani Putri Wanaliman Group, Coffee Packaging Handicrafts, Geol Crackers, where each object and tourist attraction has strengths, weaknesses, opportunities and threats in identifying potential at once in tourism development. In the tourism development strategy of Leuweunggajah village, it must improve the quality of facilities, improve human resources through various kinds of training and the support and participation of the Leuweunggajah village government in order to improve the quality of the economy of the Leuweunggajah village community.